Determinants of Cervical Cancer Risk Factors with Prevention Efforts in Women of Childbearing Age in Samapuin Village, Sumbawa Regency - Evi Gustia Kesuma; Yunita Lestari; Has'ad Rahman Attamimi (International Journal Of Health Science, 2025)
Cervical cancer remains one of the leading causes of cancer-related deaths among women, particularly in developing countries, where access to prevention and treatment options may be limited. Early detection and prevention are crucial, especially for women of reproductive age (WRA), who are considered a high-risk group for the disease. This study aims to analyze the relationship between various risk factors and preventive measures, such as Visual Inspection with Acetic Acid (VIA) tests and HPV vaccination, in Samapuin Village, Sumbawa Regency. A quantitative analytic study with a cross-sectional design was conducted, involving 109 respondents selected through total sampling. Data analysis was performed using univariate, bivariate (Chi-square test), and multivariate analysis through multiple logistic regression with the backward method. The findings indicate that certain factors, such as age at first marriage, exposure to cigarette smoke, and history of hormonal contraceptive use, were significantly associated with cervical cancer prevention efforts (p < 0.05). However, age at menarche and parity did not show significant associations. Among the factors, age at first marriage emerged as the most dominant factor influencing preventive behavior. Women who married at an older age were more likely to engage in preventive actions such as regular screening and vaccination. These results underscore the importance of addressing modifiable risk factors through targeted education and public health interventions. In conclusion, cervical cancer prevention efforts can be significantly influenced by behavioral changes related to modifiable risk factors. Public health strategies should focus on raising awareness, improving access to screening, and encouraging HPV vaccination. The active involvement of health workers is crucial in enhancing education and facilitating access to these preventive measures, ultimately reducing the burden of cervical cancer in communities.